Research on the Stability of New-type Power Systems under Gauss & Poisson Excitation - PENG Li; ZUO Xiuhan; XIE Sheng; CHEN Yongdong; LIU Jin (Kongzhi Yu Xinxi Jishu)
With the increasing proportion of renewable energy and power electronic equipment in applications, new-type power systems are bringing more external excitation with growing intensity in the development towards electrification and cleanliness. In order to reveal the influences of random factors from external excitation on the stability of new-type power systems, this paper presents a methodology of stability analysis for power systems from the perspective of numerical ranges, focusing on the Gaussian and Poisson excitation. Firstly, stochastic characteristics of Gaussian and Poisson excitation are described respectively. Then, a stochastic dynamic model is given for power systems under Gaussian and Poisson excitation, and Milstein-Euler numerical calculation method is constructed based on the predictor-corrector approach to iteratively solve the established model. The final part involves a quantitative analysis on the influence to the stability of new-type power systems in varying excitation intensity. The correctness and rationality of the stochastic dynamic model for power systems under Gaussian and Poisson excitation and the Milstein-Euler numerical calculation method were verified through analysis of numerical examples. The model and method proposed may be used as a reference for modeling and simulation of power systems under the influence of random factors, to support safe operation and optimal control.